Optimization of Natural Ventilation Openings in Mosques Based on Air Change Standards to Improve Prayer Comfort - Huda, Kumala Cahya Nurul; Augusta S, Firninda Almas; Lathifatuzzahroh, Intan; Ismail, Keysa Zafirah (Proceedings of the International Conference on Green Technology; Vol 15 No 1 (2025): Proceeding of 15th International Conference on Green Technology, 2026)
Thermal comfort in worship buildings, such as mosques, is very important to ensure that worshipers can worship solemnly and comfortably. Ulul Albab Mosque at Maulana Malik Ibrahim State Islamic University Malang is one of the buildings that require special attention in terms of natural ventilation. Its strategic location in the middle of the campus, as well as the high level of activity, makes this mosque a very important center of religious activities. However, the management of natural ventilation is often not handled properly, given the limited openings and obstructions from surrounding buildings. This study aims to optimize natural ventilation at the Ulul Albab Mosque to improve thermal comfort for users during worship activities. This research uses Computational Fluid Dynamics (CFD) simulation to model various scenarios of changes in ventilation openings. The simulation results show that the addition and strategic placement of incidental openings and vents in the mihrab, side, and back areas of the prayer room can significantly increase airflow. These additions can reduce areas with stagnant airflow and improve user comfort inside the mosque.